Artificial intelligence-assisted nursing interventions in psychiatry for oral cancer patients: A concise narrative review - Abdulmalik Fareeq Saber; Sirwan Khalid Ahmed; Safin Hussein; Karzan Qurbani (Oral Oncology Reports)
Oral cancer presents a significant global public health challenge, which is further complicated by the psychological distress experienced by patients. The integration of artificial intelligence (AI) into psychiatric nursing offers an innovative approach to improving care for oral cancer patients. This paper explores the multifaceted role of psychiatric nurses in addressing the psychological aspects of oral cancer, highlighting the transformative potential of AI in enhancing diagnostics, patient monitoring, treatment planning, and psychosocial support. AI-driven tools, such as predictive models, natural language processing, and mobile applications, provide novel means of early disease detection, risk assessment, personalized care planning, and real-time patient support. By leveraging AI, psychiatric nurses can play a crucial role in identifying oral cancer cases, assessing risks, delivering targeted interventions, and promoting patient engagement and self-management. Furthermore, AI-powered telemedicine platforms and wearable devices enable continuous care and support, particularly in remote or underserved areas, ensuring timely intervention and improving patients' quality of life. The collaboration between psychiatric nurses and interdisciplinary teams aims to utilize AI-generated insights for comprehensive care. Challenges and ethical considerations in integrating AI into healthcare include data privacy, algorithm validation, and the need for professional training.